3pK, a novel mitogen-activated protein (MAP) kinase-activated protein kinase, is targeted by three MAP kinase pathways. - Ludwig, S (1996)
Recently we have identified a mitogen-activated protein kinase (MAPK)-activated protein kinase, named 3pK (G. Sithanandam, F. Latif, U. Smola, R. A. Bernal, F.-M. Duh, H. Li, I. Kuzmin, V. Wixler, L. Geil, S. Shresta, P. A. Lloyd, S. Bader, Y. Sekido, K. D. Tartof, V. I. Kashuba, E. R. Zabarovsky, M. Dean, G. Klein, B. Zbar, M. I. Lerman, J. D. Minna, U. R. Rapp, and A. Allikmets, Mol. Cell. Biol. 16:868-876, 1996). In vitro characterization of the kinase revealed that 3pK is activated by ERK. It was further shown that 3pK is phosphorylated in vivo after stimulation of cells with serum. However, the in vivo relevance of this observation in terms of involvement of the Raf/MEK/ERK cascade has not been established. Here we show that 3pK is activated in vivo by the growth inducers serum and tetradecanoyl phorbol acetate in promyelocytic HL60 cells and transiently transfected embryonic kidney 293 cells. Activation of 3pK was Raf dependent and was mediated by the Raf/MEK/ERK kinase cascade. 3pK was also shown to be activated after stress stimulation of cells. In vitro studies with recombinant proteins demonstrate that in addition to ERK, members of other subgroups of the MAPK family, namely, p38RK and Jun-N-terminal kinases/stress-activated protein kinases, were also able to phosphorylate and activate 3pK. Cotransfection experiments as well as the use of a specific inhibitor of p38RK showed that these in vitro upstream activators also function in vivo, identifying 3pK as the first kinase to be activated through all three MAPK cascades. Thus, 3pK is a novel convergence point of different MAPK pathways and could function as an integrative element of signaling in both mitogen and stress responses.